From 1907 till 1910. Reports on the labour and socialist movement pres. by affiliated parties to the International socialist congress of Copenhague (August 28th-Sept. 3rd 1910). Pref. of the secretary of the I[nternational] S[ocialist] B[ureau] (N.pl.)
I. Great Britain